Analisis Determinan Efisiensi Kinerja Perusahaan Serta Implikasinya Dalam Penentuan Perusahaan Prioritas - Achmad Ludvy; Rissa Hanny (Musamus Journal of Business & Management, 2021)
This study aims to analyze the determinants of company performance efficiency and determine priority companies listed LQ45 Index on the IDX for 2008-2016. Company performance is measured based on liquidity, asset management, leverage, and profitability. This type of research is associative analysis, namely the analysis using the Stochastic Frontier Analysis (SFA) approach in calculating the effect of the value of financial ratios on stock prices and predicting the efficiency of company performance. The following analysis method is the Analytical Network Process (ANP), which determines the priority companies based on the efficiency value of the company's performance. The results of this study indicate a simultaneous influence of the value of financial ratios on stock prices in predicting the level of efficiency of company performance. Furthermore, the efficiency value is used as a criterion in determining priority companies, and the results show that priority companies in IDX LQ45 come from different industrial sectors.